Inappropriate Timing of Swallow in the Respiratory Cycle Causes Breathing–Swallowing Discoordination - Yagi, Naomi; Oku, Yoshitaka; Nagami, Shinsuke; Yamagata, Yoshie; Kayashita, Jun; Ishikawa, Akira; Domen, Kazuhisa; Takahashi, Ryosuke (Frontiers in Physiology, 2017)
Rationale: Swallowing during inspiration and swallowing immediately followed by inspiration increase the chances of aspiration and may cause disease exacerbation. However, the mechanisms by which such breathing-swallowing discoordination occurs are not well understood. Objectives: We hypothesized that breathing-swallowing discoordination occurs when the timing of the swallow in the respiratory cycle is inappropriate. To test this hypothesis, we monitored respiration and swallowing activity in healthy subjects and in patients with dysphagia using a non-invasive swallowing monitoring system. Measurements and Main Results: The parameters measured included the timing of swallow in the respiratory cycle, swallowing latency (interval between the onset of respiratory pause and the onset of swallow), pause duration (duration of respiratory pause for swallowing), and the breathing-swallowing coordination pattern. We classified swallows that closely follow inspiration (I) as I-SW, whereas those that precede I as SW-I pattern. Patients with dysphagia had prolonged swallowing latency and pause duration, and tended to have I-SW or SW-I patterns reflecting breathing-swallows discoordination. Conclusions: We conclude that swallows at inappropriate timing in the respiratory cycle cause breathing-swallowing discoordination, and the prolongation of swallowing latency leads to delayed timing of the swallow, and results in an increase in the SW-I pattern in patients with dysphagia.